International Influence of an Australian Nongovernment Organization in the Protection of Patagonian Toothfish - Fallon, LD; Kriwoken, LK (2004)
Soviet Union fishing fleets found Patagonian toothfish in 1985 off the Kerguelen Islands in the Southern Ocean. In a few short years, toothfish became heavily fished and the viability of the fishery was put in question. This pressure largely arose from illegal, unreported, and unregulated (IUU) fishing that undermined fisheries management by coastal states and the Convention for the Conservation of Antarctic Marine Living Resources (CCAMLR) Commission. The International Southern Oceans Longline Fisheries Information Clearing House (ISOFISH), based in Hobart, Tasmania, Australia, raised awareness about IUU fishing among governments, fishers, and the community. This article presents a case study of ISOFISH and the influence this nongovernment organization coalition exerted on the international community, including the deep-sea fishing industry, governments, and CCAMLR members, in an effort to protect toothfish stocks and reduce the incidental mortality of endangered seabirds and other nontarget marine species from longlining activities.